HNK-1 Carrier Glycoproteins Are Decreased in the Alzheimer’s Disease Brain - García-Ayllón, María-Salud; Botella-López, Arancha; Cuchillo-Ibañez, Inmaculada; Rábano, Alberto; Andreasen, Niels; Blennow, Kaj; Ávila, Jesús; Sáez-Valero, Javier (MOLECULAR NEUROBIOLOGY, 2017)
The human natural killer-1 (HNK-1), 3-sulfonated glucuronic acid, is a glycoepitope marker of cell adhesion that participates in cell-cell and cell-extracellular matrix interactions and in neurite growth. Very little is known about the regulation of the HNK-1 glycan in neurodegenerative disease, particularly in Alzheimer’s disease (AD). In this study, we investigate changes in the levels of HNK-1 carrier glycoproteins in AD. We demonstrate an overall decrease in HNK-1 immunoreactivity in glycoproteins extracted from the frontal cortex of AD subjects, compared with levels from non-demented controls (NDC). Immunoblotting of ventricular post-mortem and lumbar ante-mortem cerebrospinal fluid with HNK-1 antibodies indicate similar levels of carrier glycoproteins in AD and NDC samples. Decrease in HNK-1 carrier glycoproteins were not paralleled by changes in messenger RNA (mRNA) levels of the enzymes involved in the synthesis of the glycoepitope, β-1,4-galactosyltransferase (β4GalT), glucuronyltransferases GlcAT-P and GlcAT-S, or sulfotransferase HNK-1ST. Over-expression of amyloid precursor protein in Tg2576 transgenic mice and in vitro treatment of SH-SY5Y neuroblastoma cells with the amyloidogenic Aβ42 peptide resulted in a decrease in HNK-1 immunoreactivity levels in brain and cellular extracts, whereas the levels of soluble HNK-1 glycoproteins detected in culture media were not affected by Aβ treatment. HNK-1 levels remain unaffected in the brain extracts of Tg-VLW mice, a model of mutant hyperphosphorylated tau, and in SH-SY5Y cells over-expressing hyperphosphorylated wild-type tau. These results provide evidence that cellular levels of HNK-1 carrier glycoforms are decreased in the brain of AD subjects, probably influenced by the β-amyloid protein.